Pendampingan Penggunaan Aplikasi Turnitin dalam Meningkatkan Kualitas Karya Ilmiah Mahasiswa - Saipul Alsukri (MENARA RIAU, 2023)
Writing articles or scientific papers is an activity that cannot be avoided in the academic world. The problem is that not all writings produced can be protected from integrity violations such as plagiarism and originality of works. For this reason, training is needed to assist the Turnitin software's operation. The aim is to provide the knowledge and skills required to prevent plagiarism in student academic writing. The Participatory Action Research approach was chosen to emphasize cooperation and active participation of stakeholders in the mentoring process. Participants included study program staff, academics and lecturers in the Faculty of Economics and Social Sciences, UIN Sultan Syarif Kasim Riau. The activity was carried out using the lecture method and demonstration of the operation of Turnitin. The results show that the Participatory Action Research approach effectively promotes participants' active participation, leading to successful training sessions. The results of this activity are expected to contribute to ongoing efforts to promote responsible and ethical academic practices for students and lecturers.